Cameroon : Poverty Reduction Strategy Paper; Joint Staff Advisory Note. (IMF Staff Country Reports; Country Report, 2010)
The government of Cameroon adopted its first Poverty Reduction Strategy Paper (PRSP) to define the overall framework for its development policies. To adjust the overall objectives and address the weaknesses of the first PRSP, a new comprehensive framework, Cameroon's Strategy for Growth and Employment (DSCE), was adopted that focuses mainly on infrastructure and rural development. The DSCE aims to strengthen the macroeconomic framework, the link between DSCE, MTEF, and the annual budgets, and the implementation of governance and anticorruption programs, and also to ensure adequate resources for structural reforms.